Mysztech Solution (Mts) Point Of Sales (Pos) System - Mohamad Mohsin, Ismail (2023)
The MYSZTECH POS System with Table Layout is a comprehensive solution designed to enhance the customer experience and optimize operations for cafe and restaurant owners. Developed using the waterfall methodology and tailored to specific client requirements, this system offers a range of management features, including sales management, item management, thermal printer compatibility, discount management, tax management, and outlet management. The key highlight of this solution is its innovative table layout functionality, which enables efficient order tracking and streamlines the dining experience. With real-time insights into customer behavior and seamless table management, businesses can optimize their operations and make informed decisions to drive success in the competitive food service industry.